HUBUNGAN PENGETAHUAN DAN MINAT BIDAN DENGAN PELAKSANAAN KUNJUNGAN NIFAS DI WILAYAH PUSKESMAS BANDAR KECAMATAN BANDAR KABUPATEN BENER MERIAH - Warzukni, Seri (Universitas Prima Indonesia, 2024)
ABSTRACT Postpartum visits are a process of decision making and actions carried out by midwives during the postpartum period in accordance with their authority and scope of practice based on midwifery knowledge and tips, services during the postpartum period through home visits at least 4 times, namely 6 - 8 hours after delivery, the 6th day after delivery, the 2nd week after delivery, and the 6th week after delivery, the implementation of postpartum visits carried out by midwives is also related to knowledge and interest. This is the main cause of not implementing postpartum visits well. Research Objective: to determine the relationship between midwives' knowledge and interest and the implementation of postpartum visits. This type of research is descriptive and analytical with a cross sectional approach. The sampling method was carried out with the total population, namely by taking the entire population of midwives in the Bandar Community Health Center working area as a sample of 36 respondents. This research was carried out on April 19 2024. The results showed that 9 people (25%) had poor knowledge of midwives, 11 people had sufficient knowledge (30.6%), and 16 people had good knowledge (44.4%). while the relationship between midwife's knowledge and the implementation of postpartum visits has a significant relationship with a P-Value of 0.003. Conclusions and Suggestions there is a relationship between midwife's knowledge and the implementation of postpartum visits. Midwives' positive interest in implementing postpartum visits. amounting to 27 people (75%), and negative amounting to 9 (25%), while the relationship between midwife interest and the implementation of postpartum visits. It has a significant relationship with a P-Value value of 0.032, so it can be concluded that there is a relationship between midwife interest and the implementation of postpartum visits. From this understanding, additional information has been provided so that midwives can understand and understand how to carry out postpartum visits well. Keywords: Knowledge, Interests, Midwives, Implementation of Postpartum Visits